Method for in-situ growth of thermal shock resistant tantalum carbide coating on carbon-based substrate
The growth of porous tantalum carbide coating on the carbon-based substrate by laser chemical vapor deposition method solves the problem of mismatch between the thermal expansion coefficient between the tantalum carbide coating and the carbon-based substrate, and achieves efficient thermal shock resistance improvement and process simplification.
Patent Information
- Application Number
- CN202510382709.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-28
- Publication Date
- 2025-05-09
- Estimated Expiration
- 2045-03-28
AI Technical Summary
In the prior art, the thermal expansion coefficient between the tantalum carbide coating and the carbon-based substrate does not match, resulting in large thermal stress, prone to cracks and interface debonding, limiting the application of carbon materials in high temperature environments.
The laser chemical vapor deposition method is used to grow the porous tantalum carbide coating with a porous structure on a carbon-based substrate. By adjusting the deposition temperature and process conditions, a dense tantalum carbide coating with a lower porous upper layer is formed to relieve thermal stress and improve thermal shock resistance.
The problem of mismatch in the thermal expansion coefficient between the tantalum carbide coating and the substrate is significantly alleviated, the thermal shock resistance of the coating is improved, and the process steps are simplified, reducing production costs.
Smart Images

Figure CN119956319A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the general plating technical field of vacuum evaporation method, sputtering method, ion implantation method or chemical vapor deposition method, and specifically relates to a method for in-situ growth of a thermal shock resistant tantalum carbide coating on a carbon-based substrate. Background Art
[0002] Carbon materials, such as graphite, carbon fiber and carbon / carbon composites, are considered to be one of the most promising thermal structural materials due to their excellent high-temperature mechanical properties, such as low density, low thermal expansion coefficient, good thermal shock resistance and good heat resistance. However, carbon materials are prone to oxidation and failure at temperatures above 370°C, which greatly limits their application in advanced aircraft and other fields.
[0003] The preparation of tantalum carbide (TaC) coating on the surface of carbon material by chemical vapor deposition is an effective way to improve the ablation resistance and oxidation resistance of carbon material. Tantalum carbide has excellent oxidation resistance and mechanical properties and is widely considered to be a suitable candidate material for thermal protection coating of carbon material. However, the mismatch of thermal expansion coefficient (CTE) between tantalum carbide coating and carbon material will produce large thermal stress, which will lead to cracks and debonding of the interface between coating and substrate under severe thermal shock environment.
[0004] In order to improve the overall thermal shock resistance of the coating, there are currently two main methods: one is to deposit a layer of SiC coating between the substrate and the TaC coating as a buffer layer; the other is to deposit TaC and SiC simultaneously to obtain a TaC-SiC multiphase coating. The above method can effectively reduce the CTE mismatch between the coating and the substrate, but it requires the introduction of a second phase, the deposition process is more complicated, and the production cost is greatly increased. In addition, the compatibility between different components of the coating is poor, which reduces the long-term service stability of the product. Therefore, it is of great significance and practical value to develop a method for in-situ preparation of TaC coatings with excellent thermal shock resistance. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for in-situ growth of a thermal shock-resistant tantalum carbide coating on a carbon-based substrate in view of the above-mentioned deficiencies in the prior art. A tantalum carbide coating with good thermal shock resistance is in-situ grown on the surface of a carbon-based substrate by laser chemical vapor deposition. The carbon-based substrate does not need to be additionally treated. A tantalum carbide coating with a porous lower layer and a dense upper layer with excellent thermal shock resistance can be obtained by simply adjusting the deposition temperature. The process is simple.
[0006] In order to solve the above technical problems, the technical solution provided by the present invention is:
[0007] A method for in-situ growth of a thermal shock resistant tantalum carbide coating on a carbon-based substrate is provided, the specific steps being as follows:
[0008] 1) placing the cleaned carbon-based substrate into the deposition chamber of the laser chemical vapor deposition equipment, and adjusting the position of the carbon-based substrate so that it is within the laser coverage range;
[0009] 2) The deposition chamber is evacuated to below the vacuum threshold, H2, carbon source and carrier gas Ar containing tantalum source are introduced, and the deposition pressure is adjusted and stabilized for 1 to 5 minutes;
[0010] 3) Turn on the laser to irradiate the carbon-based substrate, so that the surface of the carbon-based substrate is heated to the deposition temperature for deposition. After the deposition is completed, TaCl5, carrier gas Ar and laser are turned off in sequence. When the temperature of the carbon-based substrate shows 150°C, H2 is turned off, and then vacuum is applied. Wait for the carbon-based substrate to cool to room temperature to obtain tantalum carbide coating material on the surface of the carbon-based substrate.
[0011] According to the above scheme, the carbon-based substrate in step 1) is a carbon / carbon composite material or a graphite substrate.
[0012] According to the above scheme, the carbon source in step 2) is methane, propane or a mixture of the two, and the tantalum source is tantalum pentachloride vapor (obtained by heating and evaporating tantalum pentachloride).
[0013] According to the above scheme, in step 2), the H2 purity is above 99 vol%, the flow rate is 500-2000 sccm, the carbon source flow rate is 300-500 sccm, the Ar flow rate is 200-500 sccm, and the tantalum source flow rate is 0.3-0.5 g / min.
[0014] According to the above scheme, the deposition pressure in step 2) is 1 to 6 KPa.
[0015] According to the above scheme, in step 3), the laser wavelength is 700-1200nm.
[0016] According to the above scheme, the deposition process conditions of step 3) are: first deposit at 1000-1200° C. for 5-10 min, then heat up to 1300-1400° C. for 10-15 min.
[0017] The present invention also includes a tantalum carbide coating with good thermal shock resistance obtained by the above method, wherein the thermal shock resistant tantalum carbide coating consists of a porous layer and a dense layer located above the porous layer, wherein the porous layer is obtained by dense growth of conical tantalum carbide crystals perpendicular to a carbon-based substrate, and the structure is dense at the bottom of the porous layer, and the rest of the porous layer forms connected or unconnected micropores between the tantalum carbide crystals.
[0018] According to the above scheme, the thickness of the porous layer is 30-50 μm, and the thickness of the dense layer is 60-80 μm.
[0019] The present invention also includes the application of the above tantalum carbide coating in aircraft anti-ablation coating.
[0020] The present invention adopts laser chemical vapor deposition to prepare a tantalum carbide porous coating material with good thermal shock resistance. The nucleation and growth process of tantalum carbide grains are controlled by adjusting the deposition process parameters. In the early stage of growth, a large number of tantalum carbide nanoparticles without preferential orientation grow on the surface of the substrate to form a dense structure. By controlling the process conditions, <111> The oriented grains grow rapidly, forming a concave-convex structure on the substrate surface. As the growth continues, due to the shadow effect, the higher <111> The oriented tantalum carbide grains prevent the precursor from reaching the concave region, so the growth of the concave region stops and a <111> The oriented side branches are formed to form a porous tantalum carbide coating. The porous coating can relieve thermal stress and improve thermal shock resistance. The process conditions are then adjusted to deposit a dense layer on the surface of the porous tantalum carbide coating. The dense tantalum carbide can effectively protect the substrate.
[0021] The beneficial effects of the present invention are as follows: 1. The bottom of the porous tantalum carbide coating material provided by the present invention in contact with the substrate is a porous structure, which can buffer thermal shock stress, and the surface is composed of dense tantalum carbide, which can provide good protection for the substrate, and can significantly alleviate the problem of mismatch between the thermal expansion coefficients of the coating and the substrate, thereby improving the thermal shock resistance of the coating. 2. The preparation method of the present invention has simple process steps, and a tantalum carbide coating with good thermal shock resistance can be obtained by simply adjusting the temperature of the deposition process, which is easy to implement. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a field emission scanning electron microscope image of a sample having a tantalum carbide coating prepared in Example 1 of the present invention;
[0023] Figure 2 This is a field emission scanning electron microscope image of the sample prepared in Example 1 after the thermal shock test;
[0024] Figure 3 This is a field emission scanning imaging image of the tantalum carbide porous coating material prepared in Comparative Example 1;
[0025] Figure 4 This is a field emission electron scanning imaging image of the tantalum carbide coating material prepared in Comparative Example 2;
[0026] Figure 5 This is a field emission electron scanning microscope image of the sample prepared in Comparative Example 2 after thermal shock testing;
[0027] Figure 6 This is a transmission electron microscope image of the tantalum carbide coating material prepared in Comparative Example 2;
[0028] Figure 7 This is a field emission scanning microscope image of the tantalum carbide coating sample of Comparative Example 3;
[0029] Figure 8This is a field emission scanning microscope image of the sample of Comparative Example 3 after thermal shock testing;
[0030] Fig. 9 The XRD patterns of the coatings prepared in Example 1 and Comparative Examples 1-3. DETAILED DESCRIPTION
[0031] In order to enable those skilled in the art to better understand the technical solution of the present invention, the present invention is further described in detail below with reference to the accompanying drawings.
[0032] Example 1
[0033] A thermal shock resistant tantalum carbide coating material, the preparation method thereof has the following specific steps:
[0034] 1) A graphite sheet (2H graphite, 15 mm in diameter and 1 mm in thickness) was cleaned by ultrasonic cleaning, and the graphite sheet was used as a substrate. The substrate was placed in a deposition chamber of a laser chemical vapor deposition device, and the position of the substrate was adjusted so that it was within the laser coverage range;
[0035] 2) The deposition chamber was evacuated to below 20Pa, and dilution gases H2 (99.999%), CH4 (99.999%) and carrier gas Ar (99.999%) containing TaCl5 vapor (TaCl5 heated to 180°C) were introduced, with H2 flow rate of 500sccm, CH4 flow rate of 300sccm, Ar flow rate of 400sccm, and TaCl5 vapor flow rate of 0.4g / min. The deposition pressure was adjusted to 2KPa and stabilized for 5 minutes;
[0036] 3) Turn on the laser to irradiate the substrate, the laser irradiation output wavelength is 1000nm, the substrate surface temperature is raised to 1100℃ for deposition, the deposition time is 7min, and then the deposition temperature is raised to 1300℃ for deposition for 10min;
[0037] 4) After the deposition is completed, the carrier gas Ar and the laser are turned off in turn. When the substrate temperature shows 150°C, the H2 and CH4 are turned off, and the substrate is vacuumed. The substrate is cooled to room temperature to obtain a tantalum carbide coating material with a porous lower layer and a dense upper layer on the substrate surface.
[0038] The field emission scanning electron microscope image of the sample with tantalum carbide coating prepared in this example is as follows: Figure 1 As shown, Figure 1 (a) is the surface morphology of the coating. Figure 1(b) is the cross-sectional morphology of the sample. It can be seen that the coating deposited on the substrate surface has a double-layer structure. The lower layer is a porous layer of tantalum carbide obtained by dense growth of conical tantalum carbide crystals perpendicular to the substrate. The porous layer has a dense structure where it contacts the substrate, and there are pores between the crystals in the direction of continued upward growth. The upper layer is a dense tantalum carbide surface layer. The thickness of the lower and upper layers are 33.65μm and 65.35μm, respectively. The deposition rate of the porous layer is 288.4μm / h, and the deposition rate of the dense layer is 653.5μm / h.
[0039] The samples of this embodiment were subjected to a thermal shock test, and the specific test method was as follows: the samples were placed in a deposition chamber of a laser chemical vapor deposition device, argon and hydrogen were introduced into the deposition chamber, the argon flow rate was 400 sccm, and the hydrogen flow rate was 500 sccm, the samples were rapidly heated to 1400°C by a laser and maintained for 5 seconds, and then the laser was turned off, and the samples were rapidly cooled to room temperature under argon and hydrogen purge, which was considered as one cycle. One thermal shock test included 10 cycles, and after the test was completed, the cracks of the coating and its bonding with the substrate were observed by a scanning electron microscope, and the thermal shock resistance of the coating was evaluated in combination with indicators such as the number and length of cracks.
[0040] The field emission scanning electron microscope image of the sample after the thermal shock test in this embodiment is as follows Figure 2 As shown, Figure 2 (a) is the surface morphology of the coating. Figure 2 (b) is the cross-sectional morphology of the sample. Microcracks can be observed on the coating surface and through cracks can be observed from the cross section, but the number of cracks is relatively small. Figure 2 (b) It can be observed that cracks are generated in the dense tantalum carbide coating on the upper layer and propagate downward, but the cracks stop propagating when they reach the porous buffer layer. This is because the porous tantalum carbide coating, as a buffer layer, effectively relieves the thermal stress between the dense tantalum carbide coating and the substrate, and the large number of voids inside the porous tantalum carbide coating prevent the propagation of cracks, effectively improving the overall thermal shock resistance of the coating.
[0041] Comparative Example 1
[0042] A tantalum carbide coating material, the preparation method of which is similar to that of Example 1, except that in step 3) the deposition temperature is 1000° C. and the deposition time is 10 min.
[0043] The field emission scanning imaging image of the tantalum carbide porous coating material prepared in this comparative example is as follows Figure 3 As shown, Figure 3 (a) is the surface morphology of the coating. Figure 3(b) is a cross-sectional morphology of the coating. It can be seen that the surface of the coating material prepared in this comparative example is pyramid-shaped. The cross section shows that the conical tantalum carbide crystals grow densely vertically to the substrate, and a dense layer is formed at the bottom of the coating. In the upper part of the coating, many feather-like branches grow on the main trunk of the tantalum carbide crystal, and a nanoporous structure is formed between the crystals. The total thickness of the coating is about 70μm, and the deposition rate is 700μm / h.
[0044] Comparative Example 2
[0045] A tantalum carbide coating material, the preparation method of which is similar to that of Example 1, except that in step 3) the deposition temperature is 1100° C. and the deposition time is 30 min.
[0046] The field emission electron scanning imaging image of the tantalum carbide coating material prepared in this comparative example is as follows Figure 4 As shown, the coating is tightly bonded to the substrate, the surface is pyramid-shaped, the cross section is dendritic, and obvious pores can be observed on the surface and cross section, indicating that the tantalum carbide coating prepared under this condition is a porous structure. The coating thickness is about 96μm, and the deposition rate is 576μm / h.
[0047] The tantalum carbide coating material sample prepared in this comparative example was subjected to a thermal shock test using the method of Example 1. The field emission electron scanning microscope image of the sample after the thermal shock test is as follows: Figure 5 As shown in the figure, the test results show that no cracks were observed on the surface and cross section of the coating material after the thermal shock test, showing excellent thermal shock resistance. During the thermal shock process, the dense structure composed of fine tantalum carbide nanoparticles at the bottom ensures that the coating is firmly bonded to the substrate, while the nanoporous structure inside the coating is conducive to relieving thermal stress.
[0048] The transmission electron microscope image of the tantalum carbide coating material prepared in this comparative example is as follows Figure 6 As shown, Figure 6 (a)-(c) are SEM and HRTEM images of the coating material. It can be observed that the tantalum carbide crystal structure is composed of a trunk and branches. There are not only a large number of gaps of varying sizes between the trunks, but also a large number of gaps of varying sizes between the branches. Figure 6 (d) High-resolution transmission electron micrograph and diffraction pattern of the trunk area. The results show that the tantalum carbide crystals are <111> Direction growth.
[0049] Comparative Example 3
[0050] A tantalum carbide coating material, the preparation method of which is similar to that of Example 1, except that in step 3) the deposition temperature is 1300° C. and the deposition time is 10 min.
[0051] The field emission scanning microscope image of the tantalum carbide coating sample prepared in this comparative example is as follows: Figure 7As shown, Figure 7 (a) is the surface morphology of the coating, Figure 7 (b) is a cross-sectional morphology of the coating, the coating thickness is about 100 μm, and the deposition rate is 1000 μm / h. The results show that the coating obtained in this comparative example is a dense structure. The sample of this comparative example was subjected to a thermal shock test using the method of Example 1. The field emission scanning microscope image of the sample after the thermal shock test is as follows: Figure 8 As shown. The test results show that microcracks can be observed on the coating surface, longitudinal cracks can be observed from the cross section, and an obvious gap is generated between the coating and the substrate, indicating that the coating has a tendency to fall off. The formation of microcracks is caused by thermal stress caused by the mismatch of thermal expansion coefficients between the tantalum carbide coating and the graphite substrate during the thermal shock test.
[0052] Fig. 9 The XRD diagram of the coatings prepared in Example 1 and Comparative Examples 1-3 shows that the tantalum carbide crystals on the coatings in Example 1 and Comparative Example 3 are randomly oriented, while the tantalum carbide crystals in the coatings in Comparative Examples 1 and 2 are <111> Select the best orientation.
[0053] The specific embodiments described above further illustrate the purpose, technical solutions and beneficial effects of the present invention in detail. For those skilled in the art, the present invention may have various modifications and changes. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for in-situ growth of a thermal shock resistant tantalum carbide coating on a carbon-based substrate, characterized in that: The specific steps are as follows: 1) placing the cleaned carbon-based substrate into the deposition chamber of the laser chemical vapor deposition equipment, and adjusting the position of the carbon-based substrate so that it is within the laser coverage range; 2) The deposition chamber is evacuated to below the vacuum threshold, H2, carbon source and carrier gas Ar containing tantalum source are introduced, and the deposition pressure is adjusted and stabilized for 1 to 5 minutes; 3) Turn on the laser to irradiate the carbon-based substrate, so that the surface of the carbon-based substrate is heated to the deposition temperature for deposition. After the deposition is completed, turn off the carrier gas Ar and the laser in turn. When the temperature of the carbon-based substrate shows 150°C, turn off the H2 and carbon source, and then evacuate, wait for the carbon-based substrate to cool to room temperature, and obtain tantalum carbide coating material on the surface of the carbon-based substrate.
2. The method for in-situ growth of a thermal shock resistant tantalum carbide coating on a carbon-based substrate according to claim 1, characterized in that: Step 1) The carbon-based substrate is a carbon / carbon composite material or a graphite substrate.
3. The method for in-situ growth of a thermal shock resistant tantalum carbide coating on a carbon-based substrate according to claim 1, characterized in that: Step 2) The carbon source is methane, propane or a mixture of the two, and the tantalum source is tantalum pentachloride vapor.
4. The method for in-situ growth of a thermal shock resistant tantalum carbide coating on a carbon-based substrate according to claim 1, characterized in that: Step 2) The H2 purity is above 99 vol%, the flow rate is 500-2000 sccm, the carbon source flow rate is 300-500 sccm, the Ar flow rate is 200-500 sccm, and the tantalum source flow rate is 0.3-0.5 g / min.
5. The method for in-situ growth of a thermal shock resistant tantalum carbide coating on a carbon-based substrate according to claim 1, characterized in that: Step 2) The deposition pressure is 1-6 KPa.
6. The method for in-situ growth of a thermal shock resistant tantalum carbide coating on a carbon-based substrate according to claim 1, characterized in that: Step 3) The laser wavelength is 700-1200nm.
7. The method for in-situ growth of a thermal shock resistant tantalum carbide coating on a carbon-based substrate according to claim 1, characterized in that: Step 3) The deposition process conditions are: first deposit at 1000-1200° C. for 5-10 min, then heat up to 1300-1400° C. for 10-15 min.
8. A thermal shock resistant tantalum carbide coating obtained according to any one of claims 1 to 7, characterized in that: The thermal shock resistant tantalum carbide coating consists of a porous layer and a dense layer located above the porous layer, wherein the porous layer is obtained by dense growth of conical tantalum carbide crystals perpendicular to a carbon-based substrate, and the structure is dense at the bottom of the porous layer, and the rest of the porous layer forms connected or unconnected micropores between the tantalum carbide crystals.
9. The thermal shock resistant tantalum carbide coating according to claim 8, characterized in that: The thickness of the porous layer is 30-50 μm, and the thickness of the dense layer is 60-80 μm.
10. Use of the thermal shock resistant tantalum carbide coating according to claim 8 or 9 in aircraft anti-ablation coating.
Citation Information
Patent Citations
Tantalum carbide composite coating as well as preparation method and application thereof
CN118851797A
Substrate comprising tantalum coating
CN119585227A
Coating material including inorganic composite coating having low elastic modulus and high hardness and method for manufacturing the same
JP2024124133A
Silicon carbide-tantalum carbide composite and susceptor
US20150321966A1
Apparatus and method for laser deposition of durable coatings
US5441569A